The influence of ultrasonic shot peening on the microstructure and fatigue behavior of TC17 alloy - Jin Cai; Hao Wu; Yongyi Tian; Xiaoxin Zhang (Scientific Reports)
Abstract This research presents a quantitative analysis of TC17 alloy subjected to ultrasonic shot peening (USP) treatment. The effects of USP treatment under different Almen intensities on surface roughness, microstructure, plastic strain range, microhardness, residual stress, fatigue behavior and strain gradient of TC17 alloy were analyzed. Results show that increasing Almen intensity from 0.15 mmA to 0.25 mmA leads to a 27% increase in surface roughness, a 12% increase in surface compressive residual stress value, a 29% increase in the depth of compressive residual stress layer, and a 6.7% increase in the maximum value of compressive residual stress. Microstructural analysis reveals material stacking, pores, and microcracks on the specimen surface and grain refinement characteristics in the surface and subsurface layers. Strain gradient analysis shows that the deformation layer depth is uniformly distributed. An increase in Almen intensity leads to a higher degree of plastic deformation and work hardening, and the increase in compressive residual stress layer depth counteracts early fatigue failure caused by high roughness.